The Impact of Dietary Intake and Physical Activity on Body Composition in Parkinson's Disease. Issue 6 (10th June 2021) - Rivadeneyra, Jessica; Verhagen, Okker; Bartulos, Monica; Mariscal‐Pérez, Natividad; Collazo, Carla; Garcia‐Bustillo, Alvaro; Calvo, Sara; Cubo, Esther
ABSTRACT: Background: Skeletal muscle loss has been associated with declining physical performance and a negative prognostic effect on falls, disability, and mortality risk in Parkinson's disease. Objectives: We aimed to analyze the clinical correlates associated with skeletal muscle wasting in Parkinson's disease. Methods: This was a cross‐sectional, case–control, observational study. We collected information on dietary intake with a 24‐hour recall questionnaire, body composition with bioelectrical impedance, motor severity with the Unified Parkinson's disease Rating Scale, and physical activity with the Global Physical Activity Questionnaire. We used multivariate linear regression analysis to analyze the sociodemographic and clinical correlates associated with skeletal muscle loss after adjusting for confounding variables. Results: Forty‐three patients with Parkinson's disease and 21 matched family members were included. Patients and family members had similar body composition, anthropometrics, and nutritional parameters. Advanced patients had similar nutrient intakes compared to patients with mild‐to‐moderate Parkinson's disease. In the multivariate linear regression analysis, female patients with low physical activity and low energy intake were more likely to have skeletal muscle loss. Conclusions: Skeletal muscle wasting is a complex multifactorial problem. Dietary strategies and physical exercise should be recommended, especially to females with Parkinson's disease, to prevent significant skeletal muscle wasting.